Cooperative research and firm performance - Reka Horvath (Hungarian Academy of Sciences, Institute of Economics, 2001)
The aim of this paper is to provide a microeconometric analysis of the impact of research joint venture participation on productivity, using a large panel of around 6200 firms. The findings of the theoretical literature on this topic are ambiguous and there are very few empirical papers analyzing this problem. I find evidence that participation in research consortia increases productivity.
Keywords: O32; L11; D24; 330; research joint ventures; firm performance; productivity